Kebijakan Dan Potensi Pajak Air Tanah Di Kota Palangka Raya - Nova Riyanti; H.M. Riban Satia; M.Nur Tanja Putra (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Investigating and understanding the potential and rules for groundwater exploitation is the goal of this study. The issue is centered on sustainable environmental policies, which might serve as an example for local governments developing groundwater utilization regulations. Observation, interviews with relevant persons, documentation, and qualitative analysis were used to acquire the information. This study concludes that the Potential for Underground Water Tax in the City of Palangka Raya is very fluctuating, decreasing from year to year, even though many underground water tax objects are inactive. Unlike to Palangka Raya, which has developed both its public and private sectors. With these facts, the policy regarding the underground water utilization system in the City of Palangkaraya is still not serious. The tax collection system policy must also prepare personnel resources who are competent and focused on analyzing tax potential, especially with the official assessment.